2017
DOI: 10.3390/ijerph14121590
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Toxic and Genotoxic Effects of Zinc Oxide Nanoparticles after Long-Term and Repetitive Exposure to Human Mesenchymal Stem Cells

Abstract: Zinc oxide nanoparticles (ZnO-NP) are widely spread in consumer products. Data about the toxicological characteristics of ZnO-NP is still under controversial discussion. The human skin is the most important organ concerning ZnO-NP exposure. Intact skin was demonstrated to be a sufficient barrier against NPs; however, defect skin may allow NP contact to proliferating cells. Within these cells, stem cells are the most important toxicological target for NPs. The aim of this study was to evaluate the genotoxic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 34 publications
(38 reference statements)
1
28
1
Order By: Relevance
“…Our study group previously demonstrated the intracellular accumulation and persistence of ZnO-NPs in hASCs after long-term cultivation [34,45]. Exposure of ZnO-NPs affected cell migration of hASCs [46], but not their ability to multidifferentiate [34,46]. The present study was conducted to add information on the effect of citrate-coated VSOPs on hASCs.…”
Section: Discussionmentioning
confidence: 76%
“…Our study group previously demonstrated the intracellular accumulation and persistence of ZnO-NPs in hASCs after long-term cultivation [34,45]. Exposure of ZnO-NPs affected cell migration of hASCs [46], but not their ability to multidifferentiate [34,46]. The present study was conducted to add information on the effect of citrate-coated VSOPs on hASCs.…”
Section: Discussionmentioning
confidence: 76%
“…After dehydration of the specimens, embedding in Epon 812 and sectioning into ultrathin slices was performed. The slides were analyzed with an EM900 electron microscope (Carl Zeiss) and photographic negatives were digitalized by scanning [13,14].…”
Section: Cell Preparation For Temmentioning
confidence: 99%
“…ZnO NP-associated toxicity of NSCs was aggravated in a concentration-dependent manner (due to the release of the Zn ions in the culture medium), whereas the size did not show a marked influence on ZnO NP toxicity [ 183 ]. The influence of the exposure time of ZnO NPs on the toxicity of hMSC was investigated [ 184 ]. In this study, exposure to high concentrations of ZnO NP and repetitive exposure to low doses led to ZnO NP-related toxicity in hMSCs, which led to the cellular accumulation of ZnO NP [ 184 ].…”
Section: Metallic Nps and Stem Cell Toxicitymentioning
confidence: 99%
“…The influence of the exposure time of ZnO NPs on the toxicity of hMSC was investigated [ 184 ]. In this study, exposure to high concentrations of ZnO NP and repetitive exposure to low doses led to ZnO NP-related toxicity in hMSCs, which led to the cellular accumulation of ZnO NP [ 184 ]. ZnO NP-exposed mouse BM-MSCs (mBM-MSCs) showed a dose-dependent toxic action, which was attributed to high ROS production and the consequent activation of the apoptotic factors, namely caspase-3 and caspase-7 ( Figure 5 ) [ 185 ].…”
Section: Metallic Nps and Stem Cell Toxicitymentioning
confidence: 99%